Impact of GGBS on the rheology and mechanical behavior of pumpable concrete - Akhlaq, Hanzlah; Peng, Tianbo; Ajmal, Muhammad Mubashir; Khan, Muhammad Salman; Riaz, Mamoon (Frontiers in Materials, 2025)
The increasing demand for high-performance pumpable concrete in large-scale infrastructure projects necessitates optimizing workability and strength while reducing environmental impact. This research explores the rheological, workability, and mechanical behavior of pumpable concrete with fractional substitution of cement by Ground Granulated Blast Furnace Slag (GGBS), aiming to enhance sustainability and performance. A total of 30 mix designs with GGBS replacements ranging from 0% to 90% were prepared, systematically optimizing the water-binder ratio (W/B) and superplasticizer dosage to maintain constant workability (i.e., 130 ± 15 mm slump value) to achieve the required pumpability. A total of 810 samples were prepared and tested to evaluate compressive strength (450 specimens at 7, 14, 21, 28, and 56 days), splitting tensile strength (180 specimens at 28 and 56 days), and flexural strength (180 specimens at 28 and 56 days). The findings show that GGBS enhances the rheological behavior of fresh concrete by lowering both plastic viscosity and yield stress, which in turn improves its flowability and pumpability. The optimal GGBS replacement level was found to be in the range of 30%–50%, where the best balance between workability and strength development was achieved. Compressive strength tests showed that while higher GGBS levels resulted in delayed early-age strength gain, long-term strength development was significantly enhanced due to pozzolanic reactions. The splitting tensile and flexural strength results followed similar trends, demonstrating optimal performance at 40% GGBS replacement. This study confirms that the controlled use of GGBS in pumpable concrete enhances both fresh and hardened properties while promoting sustainability by reducing OPC consumption and associated carbon emissions. The findings provide valuable insights for optimizing mix designs to achieve high-performance, eco-friendly pumpable concrete suitable for modern construction applications.